External enablers in existing organizations: Emergence, novelty, and persistence of entrepreneurial initiatives - Cestino Castilla, Joaquin; Naldi, Lucia; Ots, Mart (Strategic Entrepreneurship Journal, 2023)
Abstract Research Summary There is growing consensus that exogenous environmental changes can affect entrepreneurship. The external enabler framework, which provides the structures and terminology to analyze these enabling effects, has typically focused on new venture creation. In an attempt to extend the external enabler framework to corporate entrepreneurship and innovation, our longitudinal multiple‐case study explores how environmental changes enable entrepreneurial initiatives in existing organizations. Our findings contribute to the external enabler framework, corporate entrepreneurship, and innovation literature by identifying new conceptual tools to understand the enabling effect of environmental change for the emergence, novelty, and persistence of entrepreneurial initiatives in existing organizations. Managerial Summary We studied how the Covid‐19 pandemic enabled the initiation and continuation of entrepreneurial activities. Our study of eight small US‐based news companies shows that some entrepreneurial initiatives emerged as these organizations redirected their course of action toward new initiatives enabled by the changes in the external environment. Notably, the entrepreneurial initiatives that were new‐to‐the‐industry originated from ideas that were already available in some form within the organization but were not in use until the pandemic gave them a second life. Furthermore, the continuation of these initiatives depended on the persistence of the changes in the environment and on the low maintenance requirements of these initiatives in terms of time, effort, and resources.